CFD analysis of hybrid nanofluid-based microchannel heat sink for electronic chips cooling: Applications in nano-energy thermal devices. (April 2023) - Chu, Yu-Ming; Farooq, Umar; Mishra, Nidhish Kumar; Ahmad, Zubair; Zulfiqar, Fakhar; Yasmin, Sumeira; Khan, Shan Ali
Abstract: The utilize of microchannel in miniature thermal devices and microchannel heat sinks has advanced the scientific method of heat transfer to a new level, and the fields of electronic device cooling, aerospace industries, bioengineering, and materials science are all interested in furthering the technology's advancement. The microchannel has been numerically, practically, and analytically evaluated for the past three decades in order to develop models of hydraulic and heat efficiency during flowing fluid. Microchannel heat sink and novel fluids such as nanofluids are becoming well-liked. In order to recent time the full potential hybrid nanofluid in thermal exchanger has not yet been demoralized. In order to fulfill the lack of sufficient modeling data in this advanced research, the purpose of this analysis is to scrutinize computational thermal transportation features of alumina nitride (AIN)-alumina oxide ( A l 2 O 3 ) –Water hybrid nanofluid through electronic chip in six circular microchannel heat sinks. The simulation procedure is performed with volume fraction in range of 1 % to 4 % . The effects of coefficient of heat transfer, Nusselt number, Darcy friction factor, pressure drop and thermal resistance has been investigated. The single phase, laminar, incompressible and steady-state fluid flow has been numerically solved by the finite volume method with Computational Fluid Dynamic commercial software ANSYS FLUENT (R19.2) and SIMPLE algorithm.